Antibacterial Activity of Green Synthesized Copper Oxide Nanoparticles - Abed, Suha Maher; Mahmood, Yumna Shakir; Waheed, Ibrahim Fahad; Alwan, Ammar Mohammad (Iraqi Journal of Science, 2021)
This study was conducted to investigate the antibacterial activity of green synthesized copper oxide nanoparticles (CuO NPs) using Aloe vera. Initially, bacteria were collected from clinical samples of patients having otitis media infection and the isolates were identified at the species level following biochemical tests. Copper oxide nanoparticles were prepared by green synthesis using Aloe vera leaves and characterized using UV- visible spectroscopy at 260 nm peak. The shape and size were determined by using transmission electron microscopy (TEM) and the dimensions of the particles were more precisely determined by using scanning electron microscopy (SEM) and x-ray diffraction (XRD). Different concentrations of nanoparticles (25-50-75-100 µg/ml) were tested for antibacterial activity by using the well diffusion method. The results showed that the shape of CuO NPs was spherical with a size range of 40-10 0nm. The TEM images revealed average of dimensions of 32.34, 35.63, 51.85, 74.71 and 100 nm. The antibacterial activity results of the nanoparticles showed the following growth zone inhibition values for the different bacterial species used: Staphylococci aureus 17.1 mm, Pseudomonas aeruginosa 17 mm, Escherichia coli 16.8mm, Staphylococci epidermidis 16.4mm, Pseudomonas oryzihabitans 15.3mm, Klebsiella pneumonia 13.5mm, Citrobacter freundii 12.7mm, Enterobacter Cloacae 12.2 mm, Proteus vulgaris 8mm, Concerning the virulence factor production, the nanoparticle inhibited the production of biofilm and urease more than other virulence factors, such as gelatinase, hemolysin, protease and lecithinase, by some Gram negative and positive bacterial isolates.